2021
DOI: 10.3390/ijms22094476
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Compounds with Potential Therapeutic Uses from Sweet Pepper (Capsicum annuum L.) Fruits and Their Modulation by Nitric Oxide (NO)

Abstract: Plant species are precursors of a wide variety of secondary metabolites that, besides being useful for themselves, can also be used by humans for their consumption and economic benefit. Pepper (Capsicum annuum L.) fruit is not only a common food and spice source, it also stands out for containing high amounts of antioxidants (such as vitamins C and A), polyphenols and capsaicinoids. Particular attention has been paid to capsaicin, whose anti-inflammatory, antiproliferative and analgesic activities have been re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 127 publications
1
29
0
Order By: Relevance
“…Additionally, the presence of gallic acid has been reported in purple (1200 µg/g) and dark violet (1150 µg/g) bell peppers [ 35 ]. These compounds exert potent antioxidant activity against reactive oxygen species and reactive nitrogen species [ 36 ].…”
Section: Phytochemicals Present In Bell Peppersmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the presence of gallic acid has been reported in purple (1200 µg/g) and dark violet (1150 µg/g) bell peppers [ 35 ]. These compounds exert potent antioxidant activity against reactive oxygen species and reactive nitrogen species [ 36 ].…”
Section: Phytochemicals Present In Bell Peppersmentioning
confidence: 99%
“…Other bioactive compounds such as colneleic acid, capsoside A, gingerglycolipid A, and blumenol C glucoside have been qualitatively identified in red and yellow bell pepper fruits [ 36 ]. Stuliff et al [ 31 ] reported 57 glycerolipids and glycerophospholipids, two sphingomyelin compounds and ceramides in green, yellow, and red bell peppers.…”
Section: Phytochemicals Present In Bell Peppersmentioning
confidence: 99%
“…Capsicum annuum is one of the most important horticultural crops worldwide ( Qin et al, 2014 ; Guevara et al, 2021 ; Martínez-Ispizua et al, 2021 ). Belonging to the Solanaceae family, originated and putatively domesticated from Capsicum annuum L. var.…”
Section: Introductionmentioning
confidence: 99%
“…During ripening, pepper fruits undergo drastic biochemical and phenotypical changes, being the color shift from green to red the most evident since chloroplasts are transformed into chromoplasts as a consequence of the chlorophyll degradation and the biosynthesis of carotenoids, xanthophylls, and anthocyanins. In previous studies, it has been analyzed the sweet pepper fruit ripening at biochemical and molecular levels including the transcriptome ( González-Gordo et al, 2019 ), as well as the metabolism of NADPH-generating enzymes ( Mateos et al, 2009 ; Muñoz-Vargas et al, 2018 , 2020 ), ROS metabolism ( Rodríguez-Ruiz et al, 2017a , 2019 ; Chu-Puga et al, 2019 ; González-Gordo et al, 2020 , 2022a ; Palma et al, 2020a ), reactive nitrogen species ( Chaki et al, 2015 ; Rodríguez-Ruiz et al, 2017b ), the metabolome ( Guevara et al, 2021 ), and the plastidial and mitochondrial proteomes ( Rödiger et al, 2021 ; González-Gordo et al, 2022b ). However, little is known about the proteome from peroxisomes and how it can be modulated during ripening.…”
Section: Introductionmentioning
confidence: 99%